The Cambridge companion to biblical narrative - Bodner, Keith (Cambridge companions to religion, 2025)
"This Companion offers an overview and introduction to an exciting field within literary interpretation of the Hebrew Scriptures and New Testament. Designed for use in undergraduate and graduate courses, this book will serve as an excellent resource for instructors and students interested in understanding and interpreting biblical narrative"